2010
DOI: 10.1577/a08-065.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Methods Used to Mark Juvenile Chinook Salmon: Automated and Manual Marking

Abstract: Hatcheries in the U.S. Pacific Northwest are increasingly implementing programs that use an adipose fin clip and coded wire tag to mark a large number of juvenile salmonids Oncorhynchus spp. Traditionally, fin‐clipping and tagging were done by hand, but the need to mass‐mark large numbers of fish has led to the development of an automated tagging trailer system (Northwest Marine Technology, Inc.). We compared the adipose fin clip quality, coded wire tag retention, and injury rates of juvenile stream‐type sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 8 publications
1
23
1
Order By: Relevance
“…It was also interesting to note that snout had high lipid contents even in fish with low muscle lipid. In many release experiments and marking programmes salmon snouts are tagged with a coded wire (Hand et al 2010). Snouts/heads are then collected from salmon fisheries for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also interesting to note that snout had high lipid contents even in fish with low muscle lipid. In many release experiments and marking programmes salmon snouts are tagged with a coded wire (Hand et al 2010). Snouts/heads are then collected from salmon fisheries for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, fish are killed, and it is possible to sample ample amounts of the desired tissue for analysis. For example, salmon may be tagged with a coded wire tag in the snout in re lease experiments and marking programmes (Hand et al 2010), and heads or snouts of fish are collected from the salmon fishery for tag identification. Furthermore, there is also an increased demand in fish surveys for fish to be kept alive and returned quickly to the river after the sample has been taken.…”
Section: Introductionmentioning
confidence: 99%
“…Spring-run 2010 hatchery returns consisted of spring-run fish from brood years 2006-2008; marking and tagging operations in those years were done manually. Hand et al (2010) found only 70% of the manual clips rated "good" when employees had little or no experience, while 95% of automated tagging trailers clips rated "good." Thompson and Blankenship (1997) reported that 23% of Coho salmon completely regenerated their adipose fin when either the back or top two-thirds of the adipose fin was clipped.…”
Section: Discussionmentioning
confidence: 98%
“…We used coded-wire tags (CWTs; Northwest Marine Technology, Inc.) to mark blue catfish because CWTs generally have high retention rates, and automated tag applicators allowed efficient marking of large numbers of fish (Brennan et al 2007;Hand et al 2010;Simon and Doerner 2011;Lin et al 2012;Ashton et al 2014). To our knowledge, our use of CWTs in blue catfish represents the first application of these tags in this species and with relatively large (post-juvenile stage) fish.…”
Section: Fish Taggingmentioning
confidence: 99%